The Impact of Virtual Reality Training on Habituation in 3-Meter Shooting Basketball - Ahmad Latando Paturusi; Muh. Hidayat (International Journal of Experimental Sports Science Research, 2025)
Background: Habituation in shooting basketball is a critical component that determines the consistency of athletes' performance in dynamic match situations. Virtual Reality (VR) technology offers an immersive simulation environment that allows for repetition of shooting exercises under controlled and varied conditions. However, scientific research that specifically examines the impact of VR training on 3-meter distance shooting habituation in basketball athletes in Indonesia is still very limited. Objectives: This study aims to analyze the impact of the 8-week Virtual Reality training program on habituation levels, shooting accuracy, consistency of shot mechanics, and release speed in basketball athletes. Methods: A pre-experimental design of one-group pretest-posttest was used in this study. Thirty men's basketball athletes (purposive sampling) participated in a VR training program using the Meta Quest 3 headset with a simulation shooting game for 8 weeks, 3 sessions per week. Variables measured included: shooting accuracy (%), habituation index (%), release speed (ms), and release angle consistency (°). Data were analyzed using the Paired Sample T-Test (α = 0.05). Results: There was a significant improvement in shooting accuracy (pre: 48.3 ± 7.2% → post: 67.4 ± 5.8%; p = 0.000), habituation index (pre: 61.2 ± 9.4% → post: 82.7 ± 6.1%; p = 0.000), release speed (pre: 824 ± 64 ms → post: 693 ± 51 ms; p = 0.000), and release angle consistency (pre: 68.4 ± 8.7° → post: 74.2 ± 5.3°; p = 0.001). Conclusions: The 8-week Virtual Reality training program significantly improved the habituation and performance of shooting 3-meter basketball, with practical implications for coaches in designing technology-based training periodizations.